Proceso de atención de enfermería en pacientes con insuficiencia renal crónica que se realizan diálisis peritoneal - Montecinos Roman, Katherine Gisella (Machala : Universidad Técnica de Machala, 2019)
Infections (the most common known as peritonitis) is associated with peritoneal dialysis (PD) procedure performed in patients suffering from Chronic Renal Insufficiency (CRF) and considered one of the most serious complications that decreases the survival of the peritoneal membrane and worsening of the patient's prognosis, it also constitutes an important economic item to the state for hospitalization expenses, special examinations such as crops and the use of high-cost medications, without neglecting the biosychosocial affectation, disability, work absenteeism, among other sequels. Being able to recognize on time and provide timely treatment are essential for patients to continue with this type of dialysis. Renal Disease is classified into 5 stages as indicated in the Clinical Practice Guideline prepared by the Ministry of Public Health of Ecuador, these are: Stage I, Stage 2, Stage 3, Stage 4 and Stage 5, all in consideration also the Rate of Glomerular Filtration (TFG). The objective of the following updated bibliographical review is to apply the nursing care process based on the recommendations on the management of patients with Chronic Renal Insufficiency who undergo peritoneal dialysis, both ambulatory and at the hospital level. The nurse plays a fundamental role in this practice; provides his knowledge identifying problems and proposing successful solutions based on the knowledge and skills developed through his training
Las infecciones (la más común conocida como peritonitis) se asocia a diálisis peritoneal (DP) procedimiento realizado en pacientes que padecen de Insuficiencia Renal Crónica (IRC) y considerada como una de las complicaciones mas graves que disminuye la sobrevida de la membrana peritoneal y empeoramiento del pronóstico del paciente, además constituye un importante rubro económico al estado por gastos de hospitalización, exámenes especiales como cultivos y uso de medicamentos de alto costo, sin dejar a lado la afectación biosicosocial, la discapacidad, ausentismo laboral, entre otras secuelas. El poder reconocer a tiempo y brindar tratamiento oportuno son fundamentals para que los pacientes continuen con ésta modalidad de diálisis. La Enfermedad Renal se clasifica en 5 estadíos como lo indica la Guía de Práctica Clínica elaborada por el Ministerio de Salud Pública del Ecuador, estos son: Estadío I, Estadío 2, Estadío 3, Estadío 4 y Estadío 5, tomando en consideración además la Tasa de Filtración Glomerular (TFG). El objetivo de la siguiente revisión bibliográfica actualizada es aplicar el proceso de atención de enfermería basándonos en las recomendaciones sobre manejo de paciente con Insuficiencia Renal Crónica que se realiza diálisis peritoneal sea ambulatorio y a nivel hospitalario, la enfermera juega un rol fundamental en ésta práctica; brinda sus conocimientos identificando problemas y planteando soluciones acertadas en base al conocimiento y destrezas desarrolladas a traves de su formación.
Keywords: INSUFICIENCIA RENAL CRONICA; DIALISIS PERITONEAL; ATENCION DE ENFERMERIA